Development and validation of LC–MS/MS with in-source collision-induced dissociation for the quantification of pegcantratinib in human skin tumors. (February 2017) - Zangarini, Monique; Rajan, Neil; Danilenko, Marina; Berry, Philip; Traversa, Silvio; Veal, Gareth J
Aim: Pegcantratinib is a mini-PEGylated K252a derivative, under clinical evaluation as an anticancer agent acting through inhibition of the tropomyosin receptor kinase. A method for quantifying pegcantratinib in skin tumor biopsies of patients was required to determine tumor drug penetration.Methods & results: A sensitive and PEGylated molecule specific HPLC–MS/MS method coupled with in-source collision-induced dissociation was developed. The method exhibited excellent precision (coefficient of variation ≤8.5%), accuracy in the range 95–102%, high and consistent recovery and no matrix effect. The assay was linear across a range of 1–500 ng/ml, with a limit of quantitation of 2.5 ng/ml.Conclusion: We have developed and validated a method for analyzing pegcantratinib in human tumor biopsies, with the approach successfully applied to clinical trial samples.